2020
DOI: 10.14307/jfcs112.3.11
|View full text |Cite
|
Sign up to set email alerts
|

Wellness and Well-being: A Decade Review of AAFCS Journals (2009–2019)

Abstract: Well-being and wellness have long been the mantra of the family and consumer (FCS) profession (Brown, 1993). This paper shares the results of a decade review (2009–2019) of the American Association of Family & Consumer Sciences' (AAFCS) two major periodicals relative to their coverage of well-being and wellness. Specifically, we focused on the Journal of Family & Consumer Sciences (JFCS) and the Family & Consumer Sciences Research Journal (FCSRJ). Extraneous sources are cited to provide context an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 0 publications
0
5
0
Order By: Relevance
“…Educators can leverage these insights when designing and delivering personal finance courses to college students. By engaging in practical reasoning, students may ultimately enhance their prospects for better life outcomes (Kihm & McGregor, 2020).…”
Section: Discussionmentioning
confidence: 99%
“…Educators can leverage these insights when designing and delivering personal finance courses to college students. By engaging in practical reasoning, students may ultimately enhance their prospects for better life outcomes (Kihm & McGregor, 2020).…”
Section: Discussionmentioning
confidence: 99%
“…This freedom also calls for the end of "hustle culture" and of racial capitalism and its incessant demands on young people, especially young adult Latine who are expected to uphold the "American Dream" success narratives. Some scholars have talked about this as a dimension of economic wellbeing [1,3], and within the context of feeling financially secure for survivability and not necessarily great wealth [5,11]. We frame this as freedom from racial capitalism to highlight the structural nature of the issue rather than focus on how young Latine should learn to better navigate "the grind" to achieve wellbeing [9,11,12].…”
Section: Discussionmentioning
confidence: 99%
“…Wellbeing and wellness are concepts receiving much scholarly attention. They are distinct yet interconnected constructs, where "wellness is a process (people embark on a path of wellness) and wellbeing is a state at any given point in time (at the end of the path are degrees of being well)" [1]. However, in the literature, they are often used interchangeably, and as such, will be similarly referenced in this paper, though the focus here is on wellbeing.…”
Section: Wellness Wellbeing and Bienestarmentioning
confidence: 99%
See 1 more Smart Citation
“…Crockett et al (1990) reported that Home Economics administrators believed that wellness was a part of the mission, but surprisingly, few programs included wellness coursework. Further, Kilm and McGregor (2020) explored wellness and well-being in a systematic literature review. They found a scarcity of scholarship related to intellectual wellness, which is essential for practical reasoning, and political wellness needed to examine social conditions critically.…”
Section: Philosophy + Practicementioning
confidence: 99%